2014
DOI: 10.1007/s10875-014-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Neonatal UK Dried Blood Spots Using a Duplex TREC Screening Assay

Abstract: The study demonstrated that this duplex assay kit will identify all newborns with SCID as presumptive positives. The data also shows that with suitable TREC cut-off settings the number of presumptive positives from non-SCID newborns will be manageable in the context of a national screening service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 15 publications
6
43
0
6
Order By: Relevance
“…El potencial de los KRECS como marcador de trastornos del desarrollo de los linfocitos B en el ámbito del cribado neonatal sistemático ha sido comunicado previamente 13,22 . Al determinar TRECS y KRECS simultáneamente en la misma muestra, se aumenta la capacidad diagnóstica de la prueba.…”
Section: Discussionunclassified
“…El potencial de los KRECS como marcador de trastornos del desarrollo de los linfocitos B en el ámbito del cribado neonatal sistemático ha sido comunicado previamente 13,22 . Al determinar TRECS y KRECS simultáneamente en la misma muestra, se aumenta la capacidad diagnóstica de la prueba.…”
Section: Discussionunclassified
“…Более высокая частота аномальных результа-тов количества TREC у недоношенных новорож-денных отмечается во многих исследованиях [16,20,32,48]. В этом контексте незрелость иммун-ной системы как фактор, имеющий временный эффект, обусловленный гестационным возрас-том, трудно отделим от специфических факторов, связанных с состоянием здоровья недоношенных новорожденных.…”
Section: определение количества Trec и Krec в об-разцах сухих пятен кunclassified
“…UK assessments of the performance of a commercial TREC assay suggests that a cut off of 20 copies is acceptable and has shown that TREC-based screening with a duplex kit (TREC and β-Actin) should identify all newborns with SCID using a smaller DBS punch (1.5 mm in size) (this cut-off is particular for this assay and other different TREC assays may have a different cut-off; therefore, each assay will need testing to determine its own specific cut-off) [8]. This smaller punch ensures there is no leftover genomic DNA after an assay run.…”
Section: Screening Tests Being Used For Scid Nbsmentioning
confidence: 99%